(3GdMei (B42C (3dGCfHjGA h dG TjGWjf (B/s - (3GdUGaj, GdSYjOs ((3YeGf (B:s (3ecJHI OGQ GdKbGaI ,s, 1996)
(3gPG GdcJGH eLehYI ef GdGHWGd GdNGdUjf Gh ehShYI ef GdQLGd GdGSJKfGFjjf h dcfg SjJMhd aj eZGRI edjFI HGdhLhg h GdHhQJQjgGJ dQMGd h fSGA RQJ bHhQge Gh YQaJ HdOGfge Gh MGhQJge Gh LGOdJge Gh JYbHJ SjGSGJge h ge cdge HeG aj Pdc GdafGfjf h GdeKbajf efge Ydi OQLI ef GdaJfI h GdGKGQI h GdhdY h GdSdWI h GdGHOGY (B...(3aKeI aj gPg GdeZGRI ef VMc MJi GfaLQ h ef QaV GdgRjeI MJi GUHM jeTj Ydi GQHYI h ef bGOJg bOeGg Gdi GdeGajG MJi JNjd faSg Gfg GdeSjM h ef GQGO Gf jfJbe dfaSg MJi GUHM jJdGYH HGdQDSGA (B... (3ceG KeI ef hbY aj dYfI GdYGFdI h ef LejY cd TjGWjf GdYGde JMJ LfGMg h ef gRe GYfi GdGeHQGWhQjGJ h ef QGM jQbU GdGhgGe eY UGfYj GdGhgGe eY UGfYj GdGhgGe h ef jSJjbX cd UHGM Ydi acQI SbhW hGTfWf h ef GUHM WjaG jQGbU GWjGa GdMde GdHTQj h jNGa GdgHhW Gdi GdGQV (B...(3h KeI h KeI(B... s
Keywords: (3GdLZQGajGs; (3GdSjGSjhfs; (3JQGLes; (3GdJGQjNs